2021
DOI: 10.3390/ijerph182211846
|View full text |Cite
|
Sign up to set email alerts
|

Italian Children Exposure to Bisphenol A: Biomonitoring Data from the LIFE PERSUADED Project

Abstract: A human biomonitoring (HBM) study on bisphenol A (BPA) in Italian children and adolescents was performed within the LIFE PERSUADED project, considering the residing areas, sex and age. The median urinary BPA level was 7.02 µg/L, with children living in the South of Italy or in urban areas having higher levels than those residing in the North or in rural areas. Children aged 4–6 years had higher BPA levels than those aged 7–10 and 11–14 years, but no differences were detected between sexes. The exposure in Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
6
11
1
Order By: Relevance
“…However, the concentration of BPA in Italian women here measured was similar to another study conducted in Italy in the Tuscany Chianti area involving 715 adults between 20 and 74 years old, where GM of BPA was 5.14 μg/L (Galloway et al, 2010), indicating a possible peculiarity of this territory. Moreover, since similar BPA levels were found in children enrolled in LIFE PERSUADED (Tait et al, 2021), it can be hypothesized that the Italian population is more exposed to BPA, as a possible consequence of lifestyles, eating habits or environmental contamination; in this regard an important contribution could come from the elaboration of data collected in LIFE PERSUADED questionnaires (unpublished data).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the concentration of BPA in Italian women here measured was similar to another study conducted in Italy in the Tuscany Chianti area involving 715 adults between 20 and 74 years old, where GM of BPA was 5.14 μg/L (Galloway et al, 2010), indicating a possible peculiarity of this territory. Moreover, since similar BPA levels were found in children enrolled in LIFE PERSUADED (Tait et al, 2021), it can be hypothesized that the Italian population is more exposed to BPA, as a possible consequence of lifestyles, eating habits or environmental contamination; in this regard an important contribution could come from the elaboration of data collected in LIFE PERSUADED questionnaires (unpublished data).…”
Section: Discussionmentioning
confidence: 79%
“…In this paper, we report the HBM results for the mothers with comparison of exposure levels according to living areas, which complete the data already published for the children (Tait et al, 2020; Tait et al, 2021). Results of this large HBM study may support the adoption of legislative measures aimed at limiting the exposure to DEHP and BPA.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results of the LIFE PERSUADED project showed that the majority of Italian children population (4-14 years old) and women were exposed to DEHP and BPA [76,77], with measurable levels of its representative metabolites and showing a continuous and widespread exposure for DEHP (47.49 µg/L or 45.32 µg/g crea, as geometric mean, GM). Indeed, for DEHP metabolites both UHPLC/MS and GC/MS methods have been reported, although analysis by LC/MS is the most common, while for BPA both instruments have been used although the accredited method (ISO17025) is by GC/MS/MS [93].…”
Section: Discussionmentioning
confidence: 99%
“…The LIFE-PERSUADED project aimed at the biomonitoring of phthalates (DEHP metabolites) and BPA in Italian healthy non-obese children (age 4-14 years) and their mothers (900 couples) collected from 2015 to 2018 during the human biomonitoring study [75][76][77]. Moreover, we studied the DEHP and BPA exposure in children with idiopathic premature thelarche (IPT) or precocious puberty (IPP, a minimum of 30 girls in each group, aged 2-7 years) and idiopathic obesity (IO, a minimum of 30 boys and 30 girls, aged 6-10 years).…”
Section: Experimental Design 21 the Life-persuaded Projectmentioning
confidence: 99%